Radiopacities of the Jaws: Interpretation and Diagnosis. Issue 1 (March 2018) - Andrew, David
General dental practitioners are less confident at diagnosing radiopaque lesions of the jaws than radiolucent ones, possibly because the incidence of jaw radiopacities is comparatively low. The current review covers the majority of radiopaque lesions that are referred for a specialist opinion, and focuses on those lesions that occur commonly or those that mimic other diagnoses. The majority of radiopaque jaw lesions represent normal anatomy/normal variants or superimposed soft tissue calcifications that are typically of no clinical significance. Common pathological radiopacities of the jaws include sclerosing (condensing) osteitis, a response to low-grade chronic apical infection, and odontomes, a form of odontogenic hamartoma. The typical imaging appearances of these and other jaw radiopacities are discussed.